Preparation and characterization of PVC/Clay composites based on intercalated montmorillonite. - Marchena, Martín (Instituto Sabato, 2004)
During this work, several samples of organio modified-montmorillonite were prepared by modification of sodium montmorillonite using diethylenglicol and pliethylenglicol as main intercalation agents. These samples were used as fillers in plastified PVC paste and PVC suspension-type. Materials were studied using TGA, XRD, tests of thermal degradation, test of mechanical properties and test of susceptibility to solvents. Results indicated that poliethylenglicol was not useful as intercalation agent. Composites PVC/montmorillonite modified with diethylenglicol/tricresylphosphate resulted in the most interesting system because its mechanical porperties and thermal resistance.